Associação de gluteninas de alta massa molecular e qualidade de panificação em trigo: análise de proteínas e marcadores moleculares - Paro, Patricia (2011)
The wheat is a species of great importance in human nutrition, wheat grain is extracted from wheat flour used in the preparation of various food products. The rheological properties of wheat flour is a feature that determines the fate of the flour, being of great importance to this assessment. In breeding programs for wheat determining the quality of flour is essential for the development of cultivars, and it is necessary that the reading of the quality parameters are carried out early, with the use of small amounts of sample, reliable and the level of genotype. The development of this work aimed at the validation of molecular markers for selection of genotypes from high molecular weight glutenin, given their great influence on baking quality of wheat flour and check the correlation between parameters of quality of flour and the high molecular weight glutenin. Analyses were performed in the laboratory of biotechnology COODETEC using 77 samples of wheat (cultivars and lines) from program for wheat breeding of the institution, with data quality technology of wheat flour has characterized. The set of primers called Glu1-DX2-DX5 was used to select individuals that contained subunits Glu1-DX5 + Dy10 by PCR, nevertheless was necessary to make adjustments so that the marker amplified a fragment corresponding to allele Glu1-DX5. To check the reliability of molecular marker, all samples were characterized by electrophoresis of proteins by SDS-PAGE method and scores as a function of the subunits of glutenin high molecular weight they have. The results of the analysis of protein and molecular differ, indicating that the use of molecular markers should be used with any control in the PCR reaction. From the data collected and the quality of flour, the results were submitted to Pearson correlation analysis. It appears that the score of the protein is positively correlated with W, P and P / L, indicating that the composition of glutenin high molecular weight have significant influence on quality of wheat flour. Alleles Glu1-DX5 and the subunits of the A genome are positively correlated with protein scores and consequently with the wheat breadmaking. The allelic variants of the A genome were positively correlated with W and P. From the results it is concluded that the selection of genotypes with superior quality of flour can be made taking into account the high molecular weight glutenin encoded by the A and D genomes of wheat